Biomedical Engineering - Selishchev, Sergey V.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Biomedical Engineering covers recent advances in the growing field of biomedical technology, instrumentation, and administration. Contributions focus on theoretical and practical problems associated with: the development of medical technology; the introduction of new engineering methods into public health; hospitals and patient care; the improvement of diagnosis and therapy; biomedical information storage and retrieval. Biomedical Engineering is a translation of the Russian journal Meditsinskaya Tekhnika. The Russian volume-year is published in English beginning in July. All articles are peer-reviewed. Russian language information on Meditsinskaya Tekhnika is available at the following link: http://www.mtjournal.ru/.
Keywords: Engineering; Biomedical engineering; Biomaterials; Biomedical Engineering and Bioengineering; Biomaterials; Engineering, general